Perencanaan Virtualisasi Layanan Pengadaan Secara Elektronik Pemerintah Kabupaten Badung Menggunakan Metode Blue Ocean Strategy dan Balanced Scorecard - Aryawan, Made; Linawati, Linawati; Giriantari, Ida Ayu (Majalah Ilmiah Teknologi Elektro; Vol 15 No 2 (2016): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
The main obstacles holding LPSE in Indonesia today is the limited available resources (infrastructure and competent human resources) so it needs proper governance to maintain the availability of service in order to increase the procurement credibility of government goods or services. Virtualization Technology Utilization proposed as an alternative solution considering the efficiency, effectiveness and ease of maintenance, is considered able to accelerate the realization of a reliable and accountable LPSE so it can increase the participation of service users. This research discussed the Planning of Virtualization based on Blue Ocean Strategy analyses (BOS) and Balanced Scorecard (BSC), where the virtualization creates innovations value for LPSE Badung and becomes a real step towards BOS considering it has not been widely adopted by other LPSE. BOS gives a picture of the current organization and desired ideal condition, while the optimization and management of variable accuracy achieved through the implementation of Key Performance Indicators / KPI from various perspectives within the framework of the BSC. Canvas mapping strategy in this research, produce four steps framework namely: (1) the elimination step is to negate Internet access failure, (2) the step to reduce application error, access difficulties, the difficulties in operating the applications and connection interference, (3) the step to increase the availability of information, the speed and the smoothness of the transaction process, ease of complains, the quality of support services, data security system and (4)the step to create  service interference resistance. The virtualization implementation also gives a positive value towards the performance of LPSE services in terms of user satisfaction level, where in general the achievement recorded close to the value of user expectation, even in the services related to the handling of complaints, the performance achievement showed the value that exceeds user expectation. Further optimization and virtualization planning accuracy, conducted through the establishment of 11 Key Performance Indicators / KPI in 6 perspectives is the development of the four main perspectives BSC framework.
Keywords: Virtualization, Blue Ocean Strategy, Balanced Scorecard, LPSE, e-proc.